MANAJEMEN LABA PADA PERBANKAN KONVENSIONAL DAN PERBANKAN SYARIAH - Usep Syaipudin (Jurnal Akuntansi dan Keuangan (JAK), 2022)
Financial reporting using an accrual basis is preferred by conventional and Islamic banking because it is considered rational and fair in reflecting the company's financial condition although it can also provide flexibility to management in choosing accounting methods for certain purposes or earnings management. Based on the previous literature review regarding earnings management in both Conventional Commercial Banks and Islamic Commercial Banks, it is seen that the practice of earnings management is very likely to be carried out by managers as managers. The purpose of this study was to identify and analyze the differences in earnings management by conventional commercial banks and Islamic general banks. The type of data source used in this study is secondary data derived from audited published financial reports on Islamic Commercial Banks and Conventional Commercial Banks registered with the Financial Services Authority in Indonesia during the research period from 2014 to 2019. This study uses Earning Management as a variable measured by the Modified Jones Model. From this research, it can be concluded that there is a difference between the discretionary accrual ratio of conventional banks and the ratio of discretionary accruals of Islamic banks. Where Conventional Banks are higher in earning management than Islamic Banks.